Collaborative project to examine social support in elder homebound diabetics - Zink, Margo R; Gadomski, Mary; Oconnell, Patricia Buckley; Nizziherzog, Marie (Home Health Care Management & Practice, 1992)
Social support has a significant effect on the response to illness and treatment. The au thors present some of the findings and practical applications originating from a collaborative study, including a clinical indicator tool for the diabetic patient. This information gives the home health care professional an expanded knowledgebase to use in developing individualized care plans for the elder home care diabetic. © 1992, Sage Publications. All rights reserved.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-204-733-259-335 tex.type: [object Object]
Keywords: dept.nur